Clinico-epidemiological features of hypertensive subjects in Kassala town, Eastern Sudan - El Fadil M Osman; Ikhlas Suleiman; Ahmed G Alzubair (Wolters Kluwer Medknow Publications, 2007)
Objectives : To study the clinico- epidemiological profile of hypertension in a series of hypertensive patients in a town in Eastern Sudan. Methods : A sample of 242 hypertensive patients was studied using a structured questionnaire including the clinico-epidemiological features associated with hypertension. Results : Two thirds of the sample were females, 73.6% of whom were in the 35-64 year age-range; three-quarters of them had a low level of education. Significant risk factors for hypertension included positive family history of hypertension, and being from the Northern Sudan. Significantly more patients from the eastern and western regions had coronary heart disease (P<0.001). Also, significantly more patients from Western Sudan had left ventricular failure (P<0.02) and congestive heart failure (p<0.0001), while significantly more patients from Southern Sudan had nephropathy (P<0.007). Conclusions : The study reveals some clinico-epidemiological characteristics in a series of hypertensive patients in Eastern Sudan. It suggests a low rate of blood pressure control as well as ethnic variation of blood pressure control and complications.